Synthesis and Characterization of High Aluminum Zeolite X from Technical Grade Materials - Seyed Kamal Masoudian; Sepehr Sadighi; Ali Abbasi (Bulletin of Chemical Reaction Engineering & Catalysis, 2013)
Zeolites are widely used as ion exchangers, adsorbents, separation materials and catalyst due to their well-tailored and highly-reproducible structures; therefore, the synthesis of zeolite from low grade resources can be interested. In the present work, high aluminum zeolite X was prepared from mixing technical grade sodium aluminate and sodium silicate solutions at temperatures between 70°C and 100°C. The synthesized zeolite X was characterized by SEM and X-ray methods according to ASTM standard procedures. The results showed that aging of the synthesis medium at the room temperature considerably increased the selectivity of zeolite X formation. On the other hand, high temperature of reaction mixture during crystallization formed zeolite A in the product; therefore, it decreased the purity of zeolite X. In addition, it was found that increasing H2O/Na2O and decreasing Na2O/SiO2 molar ratios in the reaction mixture resulted product with higher purity. © 2013 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)